2015
DOI: 10.1158/0008-5472.can-14-2928
|View full text |Cite
|
Sign up to set email alerts
|

PLK1 and HOTAIR Accelerate Proteasomal Degradation of SUZ12 and ZNF198 during Hepatitis B Virus–Induced Liver Carcinogenesis

Abstract: Elucidating mechanisms of hepatitis B virus (HBV)-mediated hepatocarcinogenesis is needed to gain insights into the etiology and treatment of liver cancer. Cells where HBV is replicating exhibit increased expression of Plk1 kinase and reduced levels of two transcription repression factors, SUZ12 and ZNF198. SUZ12 is an essential subunit of the transcription repressive complex PRC2. ZNF198 stabilizes the transcription repressive complex composed of LSD1, Co-REST and HDAC1. These two transcription repressive com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
133
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(139 citation statements)
references
References 51 publications
5
133
0
1
Order By: Relevance
“…Transfection of cells with plasmids that express constitutively active Plk1 decreased the half-life of ZNF198 and SUZ12, which is consistent with the notion that phosphorylation and ubiquitination destabilize the proteins (H. Zhang et al, 2015). The shortened half-life was further reduced in cells overexpressing HOTAIR, but the action of the lncRNA was not dependent on Plk1.…”
Section: Hotairsupporting
confidence: 82%
See 3 more Smart Citations
“…Transfection of cells with plasmids that express constitutively active Plk1 decreased the half-life of ZNF198 and SUZ12, which is consistent with the notion that phosphorylation and ubiquitination destabilize the proteins (H. Zhang et al, 2015). The shortened half-life was further reduced in cells overexpressing HOTAIR, but the action of the lncRNA was not dependent on Plk1.…”
Section: Hotairsupporting
confidence: 82%
“…Since HOTAIR, SUZ12 and ZNF198 are all associated through interaction with the PRC2 or LSD1/Co-REST/HDAC1 complexes, a functional link between HOTAIR and the ubiquitination process was investigated (H. Zhang et al, 2015). Transfection of cells with plasmids that express constitutively active Plk1 decreased the half-life of ZNF198 and SUZ12, which is consistent with the notion that phosphorylation and ubiquitination destabilize the proteins (H. Zhang et al, 2015).…”
Section: Hotairsupporting
confidence: 59%
See 2 more Smart Citations
“…Although the expression of HOTAIR has not been explored in NAFLD, some studies underlined its role in other kinds of liver disease and HCC. Zhang et al [32] showed that HOTAIR accelerated carcinogenesis in hepatitis B-infected liver. Ding et al [33] showed that HOTAIR promote the migration and invasion of HCC cells, while Ishibashi et al [34] showed that HOTAIR expression is associated with HCC progression.…”
Section: Discussionmentioning
confidence: 99%